The Impact of Students’ Participation in School Cooperatives and Learning Outcomes in Entrepreneurship-Based Economics on Entrepreneurial Interest - Harfiani Harfiani; Erlita Erlita; Heril Heril; Hasri Hasri (Universitas Muhammadiyah Enrekang, 2025)
This study investigates the impact of students’ participation in school cooperatives and learning outcomes in entrepreneurship-based economics on students’ entrepreneurial interest at SMAN 1 Sidrap. The research is grounded in the theory that entrepreneurial interest can be developed through experiential learning and active involvement in economic activities within the school environment. A quantitative approach with an explanatory research design was employed to examine the relationships among variables. The population of this study consisted of all students in grade XI at SMAN 1 Sidrap, from which a sample was selected using proportional random sampling techniques. Data were collected through structured questionnaires and documentation of students’ learning outcomes, all of which had previously met validity and reliability requirements. The data were analyzed using multiple linear regression to determine both partial and simultaneous effects of the independent variables on entrepreneurial interest. The findings reveal that students’ participation in school cooperatives has a positive and significant effect on entrepreneurial interest. Active involvement in cooperative activities provides students with practical experiences such as basic management, financial recording, customer service, and decision-making, which contribute to the development of entrepreneurial attitudes. In addition, learning outcomes in entrepreneurship-based economics also show a positive and significant influence on students’ entrepreneurial interest. Students who achieve higher learning outcomes tend to demonstrate stronger motivation, confidence, and readiness to engage in entrepreneurial activities. Furthermore, the simultaneous analysis indicates that students’ participation in school cooperatives and learning outcomes in entrepreneurship-based economics collectively contribute significantly to entrepreneurial interest. These results emphasize the strategic role of schools in fostering entrepreneurial interest through both academic learning and non-academic activities. Strengthening the management and attractiveness of school cooperatives, along with improving the quality of entrepreneurship-oriented economics instruction, can effectively support the development of students’ entrepreneurial potential. This study is expected to provide practical implications for educators, schools, and policymakers in designing learning environments that encourage entrepreneurship among senior high school students.